Developing an ecologically and economically more stable semi-domestic reindeer management - a Finnish point of view - Kumpula, Jouko (Rangifer, 1999)
In arctic and sub-arctic regions semi-domestic reindeer management forms an important livelihood which should be able to provide enough income for herders. Reindeer management has natural limits of growth. Consequently it should be managed to optimise both the use of reindeer pastures and herder income. Reindeer pastures should be grazed at the economic carrying capabity level. This gives the maximum sustained harvest from reindeer stock and also the maximum sustained foraging from pastures. How is this to be accomplished? First, reliable knowledge about reindeer pastures in time and place is necessary: to estimate the quantity and quality of specific reindeer pastures within each management district, as well as the productive capacity and the changes in condition and productivity of those pastures. Secondly, data is needed on the accurate productivity of reindeer stock and the production costs for each management district. Thirdly, study the relationships between pasture resources and productivity of reindeer stock together with the effects of long-term reindeer densities on pasture condition and productivity. Finally, knowledge is needed about the effects of herd structure on reindeer stock productivity as well as the factors which restrict the use of reindeer pastures. Models based on adequate data could provide a useful tool for optimising the use of reindeer pastures and herder income. First the economic carrying capacity of reindeer pastures should be studied. Subsequently the economy of reindeer husbandry could be modelled with respect to reindeer stock density. Also the economy of reindeer husbandry based on different levels of feeding, and the effects of this husbandry practice on pastures, should be modelled. Models should be accurate and flexible enough to use when looking for solutions to practical questions and challenges in reindeer management.